Content-based image retrieval using colour and shape fused features - Mustaffa, Mas Rina; Ahmad, Fatimah; Mahmod, Ramlan; Doraisamy, Shyamala (Universiti Putra Malaysia Press, 2013)
Multi-feature methods are able to contribute to a more effective method compared to single-feature methods since feature fusion methods will be able to close the gap that exists in the single-feature methods. This paper presents a feature fusion method, which focuses on extracting colour and shape features for content-based image retrieval (CBIR). The colour feature is extracted based on the proposed Multi-resolution Joint Auto Correlograms (MJAC), while the shape information is obtained through the proposed Extended Generalised Ridgelet-Fourier (EGRF). These features are fused together through a proposed integrated scheme. The feature fusion method has been tested on the SIMPLIcity image database, where several retrieval measurements are utilised to compare the effectiveness of the proposed method with few other comparable methods. The retrieval results show that the proposed Integrated Colour-shape (ICS) descriptor has successfully obtained the best overall retrieval performance in all the retrieval measurements as compared to the benchmark methods, which include precision (53.50%), precision at 11 standard recall levels (52.48%), and rank (17.40).